2018
DOI: 10.1590/s1677-5538.ibju.2017.0025
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound (HIFU) as salvage therapy for radio-recurrent prostate cancer: predictors of disease response

Abstract: BackgroundSome men with localized radio-recurrent prostate cancer may benefit from salvage high-intensity focused ultrasound (HIFU). Herein, we describe oncologic outcomes and predictors of disease response after salvage whole gland HIFU from our prospective cohort.Materials and MethodsPatients with localized radio-recurrent prostate cancer were prospectively enrolled from January 2005 to December 2014. Participants had to meet both biochemical and histological definitions of recurrence. Exclusion criteria inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Moreover, HIFU shows a better risk/benefit ratio than other types of salvage therapy. Recent studies in Canada [ 41 ] and Brazil [ 42 ] confirmed that HIFU is a safe and effective option for radiorecurrent PCa.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, HIFU shows a better risk/benefit ratio than other types of salvage therapy. Recent studies in Canada [ 41 ] and Brazil [ 42 ] confirmed that HIFU is a safe and effective option for radiorecurrent PCa.…”
Section: Resultsmentioning
confidence: 99%
“…Gleason score was not a predictor for recurrent disease in our cohort. In a study by Dason et al which analyzed predictors for salvage HIFU failure with a similar composite endpoint, Gleason score was also not a significant predictor for treatment failure [15] . In contrast, another study including 290 after salvage HIFU, concluded that Gleason ≥8 vs. ≤6 (HR: 1.17, 95%CI 1.03-1.3), was a significant predictor for progression free survival.…”
Section: Discussionmentioning
confidence: 96%
“…Third, FUS can also be a good option for patients with remnants of PCa in the prostate after primary radiotherapy. However, it should be noted that previous studies have shown relatively higher rates of urinary (ranging from 32% to 36%) and rectal complications (ranging from 4% to 16%) among FUS patients on salvage therapy than among primary FUS patients [ 13 - 15 ].…”
Section: Possible Benefits Of Fusmentioning
confidence: 99%